Clinico-Hematological Evaluation of Bicytopenia in Adults: A Hospital-based Observational Study - Vidya Kuchanur; Appu Patil; Shivani S. Rao (Annals of African Medicine, 2026)
Abstract Background: Bicytopenia is defined as a reduction in any two of the three major blood cell lineages and may result from a wide spectrum of infectious, nutritional, hematological, and systemic disorders. Early identification of the underlying etiology is essential for appropriate management. Aims: To study the etiological spectrum, hematological profile, clinical presentation, and patterns of bicytopenia among patients attending a tertiary care Center. Materials and Methods: The study analyzed the clinical and hematological profile of 110 patients with bicytopenia. Patients were categorized based on age, gender, hematological parameters, etiologies, symptoms, and type of bicytopenia. Statistical analysis was performed using the Chi-square test. Results: Patients in the study had a mean age of 41.5 ± 15.42 years with female predominance (54.5%). Viral fever, including dengue, was the leading cause (23.6%), subsequently nutritional deficiency (13.6%) and sepsis (11.8%). Leukopenia with thrombocytopenia was the most common type of bicytopenia (37.3%). Fever was the predominant presenting symptom (48.2%). The type of bicytopenia showed a significant association with of underlying etiology ( P < 0.0001). Conclusion: Bicytopenia is associated with diverse etiologies ranging from transient infections to serious hematological disorders. Infectious diseases and nutritional deficiencies constituted the major causes in the present study. Recognition of hematological patterns along with systematic clinical evaluation can aid in early diagnosis and timely management.